(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
Based on the need to create a favorable economic conditions and increase competitiveness of country in the conditions of market relations, Armenia joined various regional integrational associations. After joining the EAEU there were many geopolitical changes in Armenia. Today, the consequences of these changes are mainly assessed based on the analysis of statistical data of foreign trade and foreign investment. Meanwhile, due attention is not paid to assessing the created situation, analyzing the opportunities that have arisen and using competitive advantages. The article describes the influence of geopolitical changes on the economic development and investment opportunities of the Republic of Armenia.